1993
DOI: 10.1002/1520-6629(199307)21:3<218::aid-jcop2290210306>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study on low- and high-risk hispanic high school students

Abstract: Hispanic high school students at low or high risk for drop out were followed up 1 year after their expected graduation date. Low‐risk students completed school at a significantly higher rate than high‐risk students. In addition, analysis of original predictor variables indicated graduated students' greater satisfaction with school compared with nongraduates. Implications for promoting high‐risk students' successful high school completion are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Dropouts frequently experience lifelong difficulties as a consequence of their educational status. Among the adversities they encounter are disenfranchisement from society, poor mental health, a greater likelihood of entering low-paying jobs, and unemployment (Hill & Sandfort, 1995;Reyes, 1993;Simmons, Black, & Zhou, 1991;Tidwell, 1988;Velez, 1989). The chances of experiencing such difficulties are particularly pronounced for youth from minority and low-income backgrounds, as evidenced by their comparatively higher rates of failure and dropout (Chavez, Oetting, & Swaim, 1994;Harrison, Wilson, Pine, Chan, & Buriel, 1990; U.S. Bureau of the Census, 1995).…”
mentioning
confidence: 99%
“…Dropouts frequently experience lifelong difficulties as a consequence of their educational status. Among the adversities they encounter are disenfranchisement from society, poor mental health, a greater likelihood of entering low-paying jobs, and unemployment (Hill & Sandfort, 1995;Reyes, 1993;Simmons, Black, & Zhou, 1991;Tidwell, 1988;Velez, 1989). The chances of experiencing such difficulties are particularly pronounced for youth from minority and low-income backgrounds, as evidenced by their comparatively higher rates of failure and dropout (Chavez, Oetting, & Swaim, 1994;Harrison, Wilson, Pine, Chan, & Buriel, 1990; U.S. Bureau of the Census, 1995).…”
mentioning
confidence: 99%
“…These studies were found mainly in psychology (40%) and sociology (9%) journals, with the remaining 15% coming from journals representing a variety of fields (i.e., social work, social science, demography, ethnic studies, culture, economics, child welfare, political science, and multidisciplinary studies). The first studies appeared in the early 1990s (Reyes, 1993; Reyes & Jason, 1991), though the research on Latina/o academic achievement outcomes did not become more prevalent until the early 2000s. From 2009 to 2015, published studies have been in the low double digits (between 10 and 18 articles per year) each consecutive year except for one (2010).…”
Section: Resultsmentioning
confidence: 99%
“…M. Padilla & Gonzalez, 2001). Furthermore, previous academic failures have been negatively associated with high school completion (Reyes, 1993; Zarate & Pineda, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations